An Update to Space Biomedical Research: Tissue Engineering in Microgravity Bioreactors - Abolfazl Barzegari (BioImpacts, 2012)
Introduction: The severe need for constructing replacement tissues in organ transplantation has necessitated the development of tissue engineering approaches and bioreactors that can bring these approaches to reality. The inherent limitations of conventional bioreactors in generating realistic tissue constructs led to the devise of the microgravity tissue engineering that uses Rotating Wall Vessel (RWV) bioreactors initially developed by NASA. Methods: In this review article, we intend to highlight some major advances and accomplishments in the rapidly-growing field of tissue engineering that could not be achieved without using microgravity. Results: Research is now focused on assembly of 3 dimensional (3D) tissue fragments from various cell types in human body such as chondrocytes, osteoblasts, embryonic and mesenchymal stem cells, hepatocytes and pancreas islet cells. Hepatocytes cultured under microgravity are now being used in extracorporeal bioartificial liver devices. Tissue constructs can be used not only in organ replacement therapy, but also in pharmaco-toxicology and food safety assessment. 3D models of various cancers may be used in studying cancer development and biology or in high-throughput screening of anticancer drug candidates. Finally, 3D heterogeneous assemblies from cancer/immune cells provide models for immunotherapy of cancer. Conclusion: Tissue engineering in (simulated) microgravity has been one of the stunning impacts of space research on biomedical sciences and their applications on earth.